A economia das imagens do esporte: produção, reprodução e valoração de bens imagéticos nos ambientes midiáticos dos megaeventos esportivos - Campos, Anderson Gurgel (2014)
This research investigates the management of spectacular images of the sport in mega events. The top-level modern sport, the basis of mega sports events, is a source of a complex system of production and image reproduction and social symbols, and of economized images this is, with the accumulation of values and meanings and it is also a bridge between those agents of these types of activities and their audiences, which ultimately reverts to capital and image. This issue becomes more relevant due to the fact that Brazil will host both World Cup in 2014 and Olympics in 2016. The main hypothesis of this doctoral research is that the images that circulate in these sports mega events are organized not in relation to their body related this is, athletes, local or competition but with other images, creating an imagery show that is constructed from an economic principle. This research, which aims to analyze the sport mega-events as media environments, allows us to show that there is an economy, an operating principle between play, sport and mega-events, from images. The reference here is the Greek concept of oikonomia and its derivations in economic theology, which support the idea of an economy of the image, which binds to the organization and management of pictorial resources in the relationship between the man and his imaginary. The objective is to investigate the construction of media environments and test the validity of speaking in the existence of an economy of image of the sport, responsible for the transformation of sports mega-events and their agents in goods of the consumer society. In the concept of game and sport the references are Huizinga and Caillois. For sport, the references are Bourdieu, from the concept of communication in sport, and Wulf and Gabauer on mimesis in the sports game. For concepts of image, event and apparatus, the ideas of Flusser are also crucial. And finally, from Agamben, Mondzain and Polanyi, the concept of economy of images is supported, which allows, in dialogue with the theory of the spectacle, Debord and Iconofagia by Baitello Jr., we can understand the essence of sports consumption in contemporary society